The peak performing professor : faculty guide to productivity and happiness - Robison, Susan, 1945- (San Francisco : Jossey-Bass, 2013)
"Grounded in research on neuroscience, faculty development, work productivity, positive psychology, and resilience, this faculty development guide is filled with the techniques and strategies that go beyond a discussion of work-life balance and teaching tips to offer practical tools for managing the life of the professor while maximizing his or her potential. Faculty who complete the book's exercises are able to anchor their work, roles, and use of time in their most deeply held values, to integrate their personal and professional lives into a seamless garment, and to create a legacy of a life well-lived"--
part 1. Power your work and your life with purpose -- part 2. Align your life with your power -- part 3. Connect with mutually supportive people -- part 4. Energize yourself for a long and happy career and life -- part 5. Pace your roles and responsibilities.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2013. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: College teaching; College teachers; Electronic books